FRI0222 MAGNETIC RESONANCE IMAGING OF MUSCLE INVOLVEMENT IN POLYARTERITIS NODOSA. (2nd June 2020) - Vargas Ruíz, R. D.; Gómez Rosero, J. A.; Muñoz, C.; Jaramillo Arroyave, D.; Hernandez, L.; González, L. A.; Vásquez, G.; Restrepo Escobar, M.; Vanegas, A.
Abstract : Background: muscle involvement is frequently reported in polyarteritis nodosa (PAN), mostly as myalgia, muscle swelling, and gait difficulty due to intramuscular arteries involvement, peripheral neuropathy, or myositis with slightly or no elevation of muscle enzymes. Magnetic resonance imaging (MRI) findings of compromised muscles have been reported in isolated cases, mainly as a limited form of PAN, however, muscular involvement patterns in MRI of patients with PAN have been recently described Objectives: to describe MRI of legs findings in patients with PAN in a tertiary center from Medellin-Colombia. Methods: it was performed a retrospective cross-sectional descriptive study of 15 adult patients who were clinically assessed as having PAN and who had undergone MRI of legs between January 2011 and December 2019. Characteristics already informed in previous studies, affected structures (muscle, subcutaneous tissue, and bone) and pattern of hyperintensities were described as diffuse pattern (signal alterations affecting the entire area of the involved muscle), patched pattern (areas of hyperintensities alternating areas of normal muscle signal intensity), and fluffy nodular pattern or cotton-wool appearance (round hyperintense lesions with fluffy margins centered on blood vessels). Results: clinical characteristics: myalgia, especially calf pain, was the most frequent muscular complaint; other clinical manifestations were: constitutional symptoms (80%), arthralgias or arthritis (50%), mono/polyneuropathy (33%), subcutaneous nodules (33%), livedo reticularis (20%), lower limbs ulcers (13%), abdominal symptoms (13%), and purpura (7%). MRI findings: bilateral muscular edema was found in all patients (100%), fatty infiltration (20%), edema of the subcutaneous cellular tissue (20%), and muscular atrophy (13%) were also described. A diffuse pattern occurred in 46% (n=7) of patients (figure panel A), a patched pattern (figure panel B) in 46% (n=7), and a fluffy nodular pattern or cotton-wool appearance (figure panel C) in 6% (n=1). The most frequently affected muscular group was gastrocnemius and soleus (67%), followed by anterior tibialis (27%), plantar, long peroneus, first finger flexors, and long flexors only affected in 7%. Bone involvement was found in 53%, being the tibia the most affected, followed by the fibula and the calcaneus. MRI led to guide the site of muscle biopsy to prove histological medium-size vasculitis in half of the patients. Conclusion: in patients with PAN suspicion who have muscular complaints, especially calf pain, MRI arises as an important diagnostic tool, and also as a guide to muscular biopsy to prove vasculitis. The patterns associated with PAN are diffuse, patched or fluffy nodular hyperintensities in gastrocnemius and soleus with or without bone compromise. References: [1]Kang, Y. et al. Muscle involvement in polyarteritis nodosa: Report of eight cases with characteristic contrast enhancement pattern on MRI. Am. J. Roentgenol. 206, 378–384 (2016). [2]Hofman DM, Lems WF, Witkamp TD, Putte VD, Bijlsma JW. Demonstration of calf abnormalities by magnetic resonance imaging in polyarteritis nodosa. Clin Rheumatol 1992; 11:402–404. Disclosure of Interests: None declared